PENGARUH HARGA, KUALITAS PELAYANAN, DAN SUASANA TOKO TERHADAP MINAT BELI KONSUMEN NICE SO DI TANGERANG RAYA - Qoni’ Putri Rahayu; Hidayat Syah; Abdilah Sani (Desanta Publisher, 2026)
This study aims to analyze the alleged effect of price (X1) on consumer buying interest (Y). To analyze the alleged effect of service quality (X2) on consumer buying interest (Y). To analyze the alleged influence of the shop atmosphere (X3) on consumer buying interest (Y). The method used is the quantitative method. The population in this study were nice so consumers who live in Tangerang Raya, including Tangerang district, Tangerang city, and South Tangerang. The sample used in this study amounted to 112 respondents. The sampling technique used is accidental sampling. The data collection technique used primary data in the form of a questionnaire in the form of a Google form link. The data analysis technique used is statistical analysis by utilizing smartPLS (partial least square) version 3. The results of this study indicate that price has no significant effect on consumer buying interest. Service quality has a significant effect on consumer buying interest. Store atmosphere has a significant effect on buying interest of Nice So consumers in Greater Tangerang.